Dietary Intakes, Vitamin A, and Iron Status of Women of Childbearing Age and Children 6-59 Months of Age from Akwa Ibom State in Nigeria - International Institute of Tropical Agriculture; International Food Policy Research Institute (International Food Policy Research Institute, 2015)
HarvestPlus, part of the CGIAR Research Program on Agriculture for Nutrition and Health (A4NH), seeks to improve the nutrient density of staple food crops through conventional plant breeding.the nutrient density of staple food crops through conventional plant breeding. In 2011, three first-wave varieties of yellow cassava, containing 6-7 ppm of provitamin A, were released in Nigeria, while the full target (15 ppm of provitamin A) varieties are expected to be released in 2015/2016. Initially, the target levels of provitamin A in cassava were set by using rough estimates on cassava intake (grams/day); bioconversion, the retinol equivalency of provitamin A carotenoids, and losses of provitamin A during processing and cooking. However, accurate information on the above parameters were needed to confirm our initial assumptions. A study on bioconversion was performed as well as retention studies. In the present study we aimed to assess the cassava intake and the vitamin A deficiency among women and preschool children in Nigeria. Therefore, we conducted a cross-sectional survey in rural to moderately-urbanized areas of Akwa-Ibom, a state identified as having high cassava consumption and high prevalence of vitamin A deficiency among children under the age of 5. The specific aims of the study were: 1) to quantify the cassava and nutrient intake, and 2) to assess the vitamin A and iron status among preschool children and women of childbearing age. (2015-03-24)